2007
DOI: 10.1364/oe.15.009434
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of high repetition rate regenerative amplifiers

Abstract: Dynamics features of high repetition rate continuously pumped solid-state regenerative amplifiers were studied numerically. A space independent rate equations and discrete-time dynamical system approach were used for system state evolution analysis. Regular single-energy operation, quasi-periodic pulsing and chaotic behavior regions are distinguished in space of control parameters. Diagrams of dynamical regimes comprehensively exhibiting operation features of the system are presented. Seed energy is shown to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 5 publications
1
28
0
Order By: Relevance
“…The beam profile is shown in figure 7-22 followed by the measured beam caustic depicted in figure 7-23. By varying parameters like the number of round trips and pump power, which affect the laser's bifurcation characteristics [104,110,111], the intermittent stable pulse regime of period ∆λ = 1.02 m doubling can be shifted to different single-energy ranges allowing output energies between 2 and 25 mJ at 3 kHz. For example, by using fewer round trips, the intermittent stable regime is followed by a further chaotic interval and stable output energy occurs between a lower and upper pump power limit for period doubling.…”
Section: Results Using the Long Stretchermentioning
confidence: 99%
See 1 more Smart Citation
“…The beam profile is shown in figure 7-22 followed by the measured beam caustic depicted in figure 7-23. By varying parameters like the number of round trips and pump power, which affect the laser's bifurcation characteristics [104,110,111], the intermittent stable pulse regime of period ∆λ = 1.02 m doubling can be shifted to different single-energy ranges allowing output energies between 2 and 25 mJ at 3 kHz. For example, by using fewer round trips, the intermittent stable regime is followed by a further chaotic interval and stable output energy occurs between a lower and upper pump power limit for period doubling.…”
Section: Results Using the Long Stretchermentioning
confidence: 99%
“…Already at 5 mJ pulse energy slight spectral broadening from 1.1 nm at 1 mJ pulse energy to 1.6 nm (at 5 mJ pulse energy) occurred explaining the short pulse duration of 1.3 ps. A complete theoretic comprehensive description of stability features of continuously pumped high repetition rate regenerative amplifier based on laser media with long relaxation times is given in [111]. It was shown that in the chaotic pulse build-up of regenerative amplifiers single energy areas exist.…”
Section: Wedged Diskmentioning
confidence: 99%
“…Our recent theoretical work has presented a generalized picture of stability features of a continuously pumped high repetition rate regenerative amplifier based on laser media with long relaxation time. The regions exhibiting different system behavior have been mapped in the space of non-dimensional control parameters: repetition rate and round trip number (Grishin et al, 2007). Additionally this analysis revealed the importance of the seed pulse energy and demonstrated that increase in the seed energy helps in eliminating the instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…It was later shown, but not quantified, that the seed energy also affects the onset of bifurcation, and that higher seed energies allow operation at higher repetition rates without the presence of bifurcation [4]. The first experimental hint that there is an inherently stable RT beyond the bifurcation instability, as illustrated in Fig.…”
mentioning
confidence: 99%
“…The numerical models that have been reported and used for the simulation of RAs either focused on a rather qualitative understanding of pulse instability and the underlying gain dynamics [3,4], or on the reproduction of concrete laboratory measurements [11,14,15]. In the first case, rather simplistic mathematical expressions were used, neglecting for example an explicit dependence of the pump intensity on the gain build-up.…”
mentioning
confidence: 99%